LITERATURE REVIEW: PENGARUH EDUKASI KESEHATAN REPRODUKSI TERHADAP TINGKAT PENGETAHUAN CATIN TENTANG KESIAPAN PRA-NIKAH - Meta Aprilia; Nuryati Yuningsih; Yuniati; Wahyudi (PT. Saha Kreasi Indonesia, 2025)
Premarital readiness, particularly in the domain of reproductive health, serves as a fundamental basis for building a healthy and harmonious family. However, many prospective brides and grooms still possess limited knowledge regarding comprehensive premarital preparation, especially in terms of physical, psychological, social, and economic aspects. Insufficient understanding of reproductive health may lead to various maternal health problems before, during, and after pregnancy. This study aimed to examine the effect of reproductive health education on the premarital readiness of prospective brides and grooms. A quantitative research method was employed using a pre-experimental design with a one-group pretest–posttest approach. The findings revealed a significant improvement in participants’ knowledge after receiving reproductive health education compared to before the intervention. It can be concluded that reproductive health education effectively enhances the knowledge and readiness of prospective brides and grooms in preparing for a healthy, sustainable, and high-quality marriage in the future.